Estrategias para el desarrollo comercial del estudio radiológico "Rayo Dent" de la ciudad de Machala. - Gallegos Zhigue, Mayra Sandra; Guaicha Orellana, Walter Joel (Machala : Universidad Técnica de Machala, 2024)
The general objective of the study “Strategies for the commercial development of the radiological study ‘Rayo Dent’ in the city of Machala” is to determine commercial strategies to strengthen the competitiveness and growth of the radiological center. The research analyzes the internal and external environment of the company using tools such as SWOT analysis, PESTEL and Porter's five forces. The methodology adopted is qualitative in approach, with a non-experimental and cross-sectional design. Surveys and interviews were used to collect information from customers and employees, identifying strengths, weaknesses and opportunities of the business. The target population included recurrent patients and company staff. The main findings reveal that Rayo Dent has a good reputation and trust from its customers, but faces weaknesses in its marketing strategy and digital presence. As a result, the proposal includes the implementation of digital campaigns, staff training, diversification of services and strategic alliances. It is concluded that strategic planning is key to improving the company's position in the market. It is recommended to strengthen communication with customers, optimize administrative processes and expand the range of services to ensure sustainability and growth.
El estudio “Estrategias para el desarrollo comercial del estudio radiológico ‘Rayo Dent’ de la ciudad de Machala” tiene como objetivo general determinar estrategias comerciales que fortalezcan la competitividad y crecimiento del centro radiológico. La investigación analiza el entorno interno y externo de la empresa mediante herramientas como el análisis FODA, PESTEL y las cinco fuerzas de Porter. La metodología adoptada es de enfoque cualitativo, con un diseño no experimental y transversal. Se utilizaron encuestas y entrevistas para recopilar información de clientes y empleados, identificando fortalezas, debilidades y oportunidades del negocio. La población objetivo incluyó pacientes recurrentes y personal de la empresa. Los principales hallazgos revelan que Rayo Dent cuenta con buena reputación y confianza por parte de sus clientes, pero enfrenta debilidades en su estrategia de comercialización y presencia digital. Como resultado, la propuesta incluye la implementación de campañas digitales, formación del personal, diversificación de servicios y alianzas estratégicas. Se concluye que la planificación estratégica es clave para mejorar la posición de la empresa en el mercado. Se recomienda fortalecer la comunicación con los clientes, optimizar los procesos administrativos y ampliar la oferta de servicios para garantizar sostenibilidad y crecimiento.
Keywords: ESTRATEGIAS COMERCIALES; COMPETITIVIDAD; RADIOLOGÍA; CRECIMIENTO EMPRESARIAL